2021
DOI: 10.4049/jimmunol.2001420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cellular and Serological Responses to Acute SARS-CoV-2 Infection Demonstrates the Functional Importance of the Receptor-Binding Domain

Abstract: This information is current as the Receptor-Binding Domain Demonstrates the Functional Importance of Responses to Acute SARS-CoV-2 Infection Evaluation of Cellular and Serological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…We have recently reported that RBD-specific MBCs upregulate the activation marker CD71 during acute COVID-19. 4 To determine the duration of activation, we assessed CD71 expression in RBD-binding and non-RBD-binding MBCs following SARS-CoV-2 infection and vaccination (Figure 2). One to two months after infection, a significantly higher percentage of RBD-specific MBCs retained expression of CD71 compared with their non-RBD-binding counterparts (p < 0.0001).…”
Section: Rbd-specific Mbcs Exhibit Sustained Activation As Measured B...mentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that RBD-specific MBCs upregulate the activation marker CD71 during acute COVID-19. 4 To determine the duration of activation, we assessed CD71 expression in RBD-binding and non-RBD-binding MBCs following SARS-CoV-2 infection and vaccination (Figure 2). One to two months after infection, a significantly higher percentage of RBD-specific MBCs retained expression of CD71 compared with their non-RBD-binding counterparts (p < 0.0001).…”
Section: Rbd-specific Mbcs Exhibit Sustained Activation As Measured B...mentioning
confidence: 99%
“…1 In numerous study cohorts, overwhelming evidence has illustrated the importance of antibodies targeting the trimeric spike (S) protein on the viral surface, especially the receptor-binding domain (RBD), in controlling SARS-CoV-2 infections. [2][3][4][5][6] RBD-specific antibodies in circulation correlate strongly with viral neutralization across infection cohorts, 7,8 and monoclonal antibodies derived from RBD-specific memory B cells generated during infection have been consistently characterized as potent neutralizers with several either approved for use or currently in clinical trials for treatment of coronavirus disease 2019 (COVID-19). 3,[5][6][7] Given the clear importance of RBD-specific antibodies in the protective immune response to infection, eliciting a similar antibody repertoire through vaccination was hypothesized to provide comparable immunity.…”
Section: Introductionmentioning
confidence: 99%
“…While analyzing RBD specific switched memory B cells, this also showed a similar pattern to antibodies in terms of isotype. RBD specific IgG memory B cells are dominated followed by IgA and then IgM type [ 36 ].…”
Section: B Cells Response During Covid-19 Infectionmentioning
confidence: 99%
“…Both antigen targets were used previously for evaluating prior infection with SARS-CoV-2 on the basis of serum antibody reactivity [74,75]. Additionally, serum antibody reactivity against the RBD protein is a strong predictor of neutralizing activity [75,76]. As shown in Figure 1A, direct capture of the RBD protein at 10 µg/mL to the assay membrane failed to yield bright and welldefined IgG + FluoroSpots following overnight incubation of pre-stimulated PBMC from four recovered COVID-19 donors.…”
Section: Affinity Tag Capture Of Sars-cov-2 Spike Proteins Improves Antigen-specific Fluorospot Assaysmentioning
confidence: 99%